Geochemical and Mineralogical Analysis of Mining Tailings in Mimika Regency for Reutilization Potential Evaluation - Nilam Sry Putri; Abd Rahim (Universitas Panca Marga, 2025)
This study characterizes the geochemical, mineralogical, and morphological properties of mine tailings along the Kali Kabur River in Mimika Regency, Central Papua. The tailings, generated by mining activities, contain valuable metallic minerals, including iron (Fe), copper (Cu), and titanium (Ti). Using X-Ray Fluorescence (XRF), X-Ray Diffraction (XRD), and Scanning Electron Microscope–Energy Dispersive X-Ray Spectroscopy (SEM–EDS), we identified major oxides (Fe₂O₃, SiO₂, CaO) and minerals (quartz, magnetite, ilmenite, chalcopyrite). Results indicate that the tailings possess potential for reutilization as secondary resources for metal extraction and as raw materials for iron sand production. This research provides novel insights into sustainable tailings management and offers guidance for local industries in the reutilization of mining waste, contributing to circular economy practices.